Menіngkatan HasіI BeIajar pada PembeIajaran Matematіka KeІas 1 SDІT Permata Hatі Model Kooperatіf Tipe NHT - Laila Rokhma; Kharisma Pratidina (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to improve student learning outcomes in mathematics subjects on data collection material with the cooperative learning model type number head together (NHT) at SD Islam Terpadu Permata Hati Batang class 1 in the 2024/2025 academic year. The background of this study is the low student learning outcomes are caused by teachers who do not provide enough motivation and the lack of variation in learning models that teachers use in classroom learning. This study was conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of this study were 26 students in grade 1. Data collection techniques were carried out through observation, interviews, tests, and presentations. This study applies the Number Head Together (NHT) model. In cycle 1, the percentage of student learning completeness reached 76.9% or 20 students then increased to 96.1% in cycle 2 or 25 children who experienced completeness. Thus, it can be concluded that the application of the cooperative learning model Type Number Head Together (NHT) can improve student learning outcomes on Data Collection material in grade 1 of SD Islam Terpadu Permata Hati Batang Regency